Promoting assessment for learning through curriculum-based performance standards: teacher responses in the Northern Territory of Australia. Issue 1 (2nd January 2017) - Fenwick, Lisl
ABSTRACT: Governments in Australia claim that standards-based reforms to schooling will result in greater use of assessment for and as learning. This study analyses the assessment practices that evolved within the planned curricula for senior secondary schooling in the Northern Territory of Australia during standards-based reforms. Case-study methodology was used, with each of the six teachers participating forming one case. The data collected and analysed included the texts created by the six participating teachers from a range of subject areas as they planned to enact the new curriculum. Semi-structured interviews were also conducted with each of the six teachers. The findings indicate that the inclusion of subject-based performance standards in the curriculum for senior schooling did not result in teachers planning a curriculum that included assessment practices for actively engaging students in learning.